Respons Kekebalan Ayam IPB D1 yang Memiliki Gen TLR4 terhadap Infeksi Bakteri Salmonella enteritidis (IMMUNE RESPONSE OF IPB D1 CHICKENS WITH TLR4 GENES AGAINST SALMONELLA ENTERITIDIS BACTERIAL INFECTION) - Susanti, Fitria; Murtini, Sri; Wibawan, I Wayan Teguh (Jurnal Veteriner, 2020)
Faculty of Animal Science, IPB University has developed new trait of chicken named IPB D1 traits. The chicken is a crossbreed chicken between male F1 PS (Pelung x Sentul) with F1 female (Kampung x parent stock Cobb). The IPB D1 chickens aims to produce the local commercial meat type, which adapted to traditional or semi intensive management (back yard). Salmonellosis is one of the bacterial disease that commonly infected poultry, therefore a study was conducted to determine the immune response of IPB D1 chickens to these disease using genetic markers, namely TLR4 gene (Toll-Like Receptor 4). TLR4 gene is one of the genes that control chicken resistance to Gram negative bacteria infection, through non-specific immune responses, one of Gram negative bacteria is Salmonella enteritidis. The aim of this study was to determine of TLR4 gene and their role in immunity of IPB D1 chickens against S. enteritidis infection. As much as 11 chickens were use in this study. This research was carried out through several stages of i.e determination of the TLR4 gene by PCR and sequencing and observing its immune response through the number of leukocyte, leukocyte differentiation and other hematology profile. Humoral immunity response against S. enteritidis were observe by clearance test before and after challenged with S. enteritidis. The results of this study indicate that IPB D1 chickens which have TLR4 genes (genotype GG and AG) were resistance against S. enteritidis based on the leukocyte, hematology profile and humoral immunity.